2010
DOI: 10.1007/s10637-010-9601-5
|View full text |Cite
|
Sign up to set email alerts
|

Diarylheptanoid hirsutenone enhances apoptotic effect of TRAIL on epithelial ovarian carcinoma cell lines via activation of death receptor and mitochondrial pathway

Abstract: Tumor necrosis factor (TNF)-related apoptosis inducing ligand (TRAIL) induces apoptosis in various cancer cells. Diarylheptanoids such as hirsutenone and oregonin have been shown to have anti-inflammatory and anti-tumor effects. However, it is still unknown by which mechanism diarylheptanoids induce cell death. In addition, the effect of hirsutenone on TRAIL-induced apoptosis in the human epithelial ovarian carcinoma cell lines is unknown. To assess the apoptosis promoting effect of hirsutenone, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Cumulative evidences suggest that HTN has bioactive properties as a diarylheptanoid and plays a key role in inducing tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-dependent apoptosis and in the inhibition of T cell-dependent cytokines, such as IL-2, 4, 5, 10, 13, and IFNγ. [13][14][15] We further demonstrated that HTN inhibited IFNγ-related gene expression in mouse splenocytes. Therefore, in this study, we investigated whether HTN effectively inhibits osteoclastogenesis by blocking the expression of T cell-mediated cytokines via indirectly the inactivation of T cells or directly attenuating osteoclastogenesis, thus indicating potential therapeutic advantages for bone resorption.…”
mentioning
confidence: 67%
“…Cumulative evidences suggest that HTN has bioactive properties as a diarylheptanoid and plays a key role in inducing tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-dependent apoptosis and in the inhibition of T cell-dependent cytokines, such as IL-2, 4, 5, 10, 13, and IFNγ. [13][14][15] We further demonstrated that HTN inhibited IFNγ-related gene expression in mouse splenocytes. Therefore, in this study, we investigated whether HTN effectively inhibits osteoclastogenesis by blocking the expression of T cell-mediated cytokines via indirectly the inactivation of T cells or directly attenuating osteoclastogenesis, thus indicating potential therapeutic advantages for bone resorption.…”
mentioning
confidence: 67%
“…Rakesh Goel and Barbara Vanderhyden (Ottawa Hospital Cancer Center, Ottawa, ON, Canada) and cultured previously as reported (19, 20). OV2008 and C13 cells were cultured in RPMI, whereas OVCAR-433, A2780s, A2780cp, Hey, Occ-1, SKOV3, and OVCAR-432 were cultured in DMEM, supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…sibirica (17). Evidence suggests that hirsutenone exhibits numerous bioactive properties, including the ability to suppress T cell activation and induce TRAIL-dependent apoptosis (18, 19). However, the effect of hirsutenone on CDDP sensitivity in cancer cells has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Galangal, the rhizome of Alpinia officinarum Hance (Zingiberaae), is a spice widely used in Europe and China for over 1000 years. Phytochemical studies of this medicinal plant have led to the isolation of many diarylheptanoids (curcumin analogs) that possess diverse pharmacological effects such as antiemetic (Shin et al, 2002;Yang et al, 2002), anti-inflammatory (Li et al, 2011;Matsuda et al, 2006), anti-tumor (Chen et al, 2015;Lee et al, 2012;Matsuda et al, 2009), and anti-oxidant activities (Kose et al, 2015;Riethmuller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%